The reckoning at Gossamer Pond - Wright, Jaime Jo (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2018)
aIn modern-day Gossamer Grove, Wisconsin, an inheritance forces Annalise Forsythe to face the town's dark secrets, while a century earlier amid the arrival of revivalists in Gossamer Grove, newspaperwoman Libby Sheffield works with a deacon's son to investigate his father's death.
aIncludes questions for discussion (pages 343-344).
Keywords: aMurder -- Investigation -- Fiction; aInheritance and succession -- Fiction; aRevivals -- Wisconsin -- Fiction; aSecrecy -- Fiction; aWisconsin -- Fiction